DETERMINANT FACTORS OF FINANCIAL REPORTING QUALITY IN LOCAL GOVERNMENT: THE EVIDENCE FROM PUBLIC SECTOR IN INDONESIA - Prawati, Levana Dhia; Murwaningsari, Etty (Journal of Applied Finance and Accounting, 2024)
This study aims to examine the effects of spending plan composition elements, regional wealth, local government features, and the characteristics of regional government leaders on the quality of local government financial reports in Indonesia, as well as the moderating effect of financial performance. The research utilized Multinomial Logistic Regression with Pooled Data for hypothesis testing. This analysis draws on 1089 Regional Government Financial Reports from around Indonesia in 2021-2023.We utilize the audit opinion type as an indicator of reporting quality, where an unqualified opinion signifies the highest level of quality, and a disclaimer of opinion indicates the lowest quality. Two ratios were developed based on the financial budget by local government to measure financial performance, which are the Routine Ability Index Ratio (RAIR) and Budget Effectiveness Ratio (BER). The findings of this study, the regional wealth factor, and the proficiency of regional government officials affect the quality of regional financial reporting (FRQ). This research has implications for central government policies in examining the quality of regional financial reporting. The first implication of this study reveals that the wealthier a regional government is, the higher the quality of its financial reporting tends to be. Second, a leaderâ€™s years of experience in governing a region influence the quality of his regional financial report.Â  This implies a longer leadership period influences better performance.